Cultural Dynamics of Intimacy in Airline Companies: A Case Study of Qatar Airways - RR. Pangestuti Hardiyanti Putri Ning Gusti; Yohanes Kristanto; Yayu Indrawati (CV. AFDIFAL MAJU BERKAH, 2023)
Qatar Airways is an airline that has its head office in Doha and has various employees from various countries. This research raises cultural intimacy within airline organizations. The research method used is a qualitative research method with thematic analysis techniques. The informant determination technique in this study used a purposive sampling technique. The results of the study indicate that cultural intimacy within Qatar Airways requires additional training to maintain the existence of the airline's employee performance. The organizational culture that occurs within the company shows that all key informants can follow the organizational culture that exists within the company. Communication that occurs between employees from various countries shows the result that communication misunderstandings often occur due to cultural differences.